2015
DOI: 10.4999/uhod.15838
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Physicians’ Preferences for Approaches to Bone Metastases Treatment in Turkey

Abstract: Bone metastases and associated skeletal-related events (SREs) are common in patients with advanced breast, lung, and prostate cancer. Bone-targeted agents (BTAs) are available for the treatment of bone metastases, but little is known about patients' and physicians' preferences for the various attributes of these agents. We evaluated preferences for BTAs used to prevent SREs among patients with bone metastases and physicians involved in treating such patients in Turkey. Participants completed an online discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Piloting in all target groups was more common (12 of 24 studies reporting piloting), and a number of studies that did not report generating attributes in all groups reported piloting their survey in all respondents. 40 42 47 50 52 …”
Section: Resultsmentioning
confidence: 99%
“…Piloting in all target groups was more common (12 of 24 studies reporting piloting), and a number of studies that did not report generating attributes in all groups reported piloting their survey in all respondents. 40 42 47 50 52 …”
Section: Resultsmentioning
confidence: 99%